Air travel in patients suffering from pulmonary hypertension: a prospective, multicentre study - Yogeswaran, Athiththan; Grimminger, Jan; Tello, Khodr; Becker, Lukas; Seeger, Werner; Grimminger, Friedrich; Sommer, Natascha; Ghofrani, Hossein A.; Lange, Tobias J.; Stadler, Stefan; Olsson, Karen; Kamp, Jan C.; et al. (Pulmonary circulation, 2024)
The PEGASUS study is the first multicentric and prospective assessment of the safety of air travel flying in pulmonary hypertension (PH) (NCT03051763). Data of air travel from 60 patients with PH was available. No severe adverse events occurred. Nine patients self-reported mild adverse events during flight (13%), while after landing, 12 patients reported events (20%). Solely one patient (2%) had an adverse event leading to medical consultation. In patients with PH and World Health Organization functional classes II and III, air travel was safe.
Gesehen am 29.09.2025